Beyond CTLA-4 and PD-1: Novel Insights into MAO-A as a Next Generation Immune Checkpoint Modulator for Cancer Immunotherapy - Maity, Prajna; Sur, Debjeet (Current Cancer Drug Targets, 2025)
Immune checkpoint blockade (ICB) has fundamentally transformed cancer treatment by unlocking the potency of CD8+ T cells by targeting the suppression of the CTLA-4 and PD-1/PD-L1 pathways. Nevertheless, ICBs are associated with the risk of severe side effects and resistance in certain patients, driving the search for novel and safer immune checkpoint modulators. Monoamine Oxidase A (MAO-A) plays an unexpected role in the field of cancer. Recent research has unveiled its dual nature: in the brain, it breaks down neurotransmitters, impacting mood and behaviour, while in tumours, its role takes a more complex turn. The involvement of MAO-A in the tumour microenvironment is crucial, affecting oxidative stress, hypoxia, and immune cell behaviour. Specifically, the regulation of tumour-associated macrophages (TAMs) and their polarisation underscores their potential as targets for cancer immunotherapy. MAO-A inhibition reprograms TAMs, shifting them from an immunosuppressive to an immunostimulatory state, thereby enhancing the activity of tumour-infiltrating CD8+ T cells. Interestingly, the presence of MAO-A in CD8+ T cells suggests its potential as a target for novel ICB therapy. This review lays the groundwork for a deeper understanding of the therapeutic potential of MAO-A by examining the intricate landscape of its role in cancer immunology. We envision a future in which harnessing the power of CD8+ T cells through optimised MAO-A targeting might lead to safer and more effective cancer treatments, offering hope for countless patients.
Keywords: cancer